A hedonic model on bred heifer prices: auction, heifer, genetic, and reputation effects considered - Wingert, Isaac (My University, 2024)
In a highly variable and differentiated industry such as cattle production, producers constantly face management decisions regarding their operation. Two of the most critical questions a producer will ask are: who is the buyer of their cattle, and what qualities and characteristics should their product contain to attract multiple buyers? The paper uses hedonic modeling to estimate marginal implicit values of characteristics of bred heifer sales to determine qualities and characteristics buyers demand. The sales data encompasses 10 years of transactions for Show-Me-Select bred heifer sales. Emphasis is on estimating implicit values of production and phenotypic factors, allowing for a deep analysis of estimated progeny differences, breed traits, and reputation effects. Sellers can self-select into production, genotypic, and phenotypic characteristics, so the premiums and/or discounts associated with artificial insemination and high-accuracy traits will be assessed. The value of this self-selection has been researched across sale barns and, to some extent, this group of sales; however, using newer data, this research project seeks to delve deeper into the value of these traits and characteristics and update past findings.
Keywords: Bred heifers; Hedonic modeling; Expected progeny differences; Genetic traits